2013
DOI: 10.1002/eji.201242730
|View full text |Cite
|
Sign up to set email alerts
|

Tetraspanin CD37 contributes to the initiation of cellular immunity by promoting dendritic cell migration

Abstract: Previous studies on the role of the tetraspanin CD37 in cellular immunity appear contradictory. In vitro approaches indicate a negative regulatory role, whereas in vivo studies suggest that CD37 is necessary for optimal cellular responses. To resolve this discrepancy, we studied the adaptive cellular immune responses of CD37 −/− mice to intradermal challenge with either tumors or model antigens and found that CD37 is essential for optimal cell-mediated immunity. We provide evidence that an increased susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
52
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 43 publications
(88 reference statements)
6
52
0
Order By: Relevance
“…In vitro leukocyte adhesion was examined using a whole blood flow chamber assay, as described previously (23,26), with some modifications. Blood was harvested from anesthetized mice by cardiac puncture, diluted 1:10 in HBSS, and perfused at a physiological shear rate of 2 dynes/cm 2 at 37˚C through a parallel flow chamber apparatus (Glycotech, Rockville, MD) assembled over 35-mm Petri dishes precoated with P-selectin (1 mg/ml), CXCL1 (5.2 nM), and either mouse ICAM-1-Fc or Fc (9 nM; all reagents were from R&D Systems).…”
Section: Flow Chamber Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro leukocyte adhesion was examined using a whole blood flow chamber assay, as described previously (23,26), with some modifications. Blood was harvested from anesthetized mice by cardiac puncture, diluted 1:10 in HBSS, and perfused at a physiological shear rate of 2 dynes/cm 2 at 37˚C through a parallel flow chamber apparatus (Glycotech, Rockville, MD) assembled over 35-mm Petri dishes precoated with P-selectin (1 mg/ml), CXCL1 (5.2 nM), and either mouse ICAM-1-Fc or Fc (9 nM; all reagents were from R&D Systems).…”
Section: Flow Chamber Assaymentioning
confidence: 99%
“…CD37 has also been shown to control functions in T cells and dendritic cells (19)(20)(21)(22). Notably, we recently demonstrated that CD37 promotes migration of dendritic cells (23). CD37 is also expressed in granulocytes (24), but its role in these cells has not been examined.…”
mentioning
confidence: 99%
“…In APCs, tetraspanins have been implicated in many facets of biology including pattern recognition (12), Ag presentation (13), and cell migration (14). A role for tetraspanins in Ag processing is suggested both by their presence in MHC class II compartments, where they associate with MHC class II and the peptide editors HLA-DM and HLA-DO (15)(16)(17), and by their association with MHC I and II at the cell surface (15,18).…”
mentioning
confidence: 99%
“…In vivo DC migration was studied by FITC-painting experiments, as described previously (29). Briefly, abdominal skin was shaved prior to applying a FITC solution.…”
Section: Fitc Paintingmentioning
confidence: 99%
“…Ear emigration assays were performed as described previously (29). Briefly, dorsal and ventral skin sheets were placed in medium containing 1 mg/ml LPS alone or LPS and 1 mg/ml CCL21 and cultured for 48 h. Emigrated DCs were quantified using flow cytometry.…”
Section: Ear Emigrationmentioning
confidence: 99%